2020
DOI: 10.3389/fnagi.2020.603854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alzheimer's Disease and Parkinson's Disease in China: An Updated Systematical Analysis

Abstract: Background: Alzheimer's disease (AD) and Parkinson's disease (PD) are two major neurodegenerative diseases worldwide. Demographic aging is in rapid progress in China. Up-to-date estimates of AD and PD prevalence have not been provided.Methods: Studies that reported the prevalence of AD and PD in China were identified via a systematic database search from 1985 to 2018. Meta-analysis, local polynomial regression and autoregressive integrated moving average model were used for analyses.Results: A total of 99 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…The annual total costs are predicted to reach United States $507.49 billion in 2030 and United States $1.89 trillion in 2050 (Jia et al, 2018). Taken together, the above statistics indicate that AD not only affects morbidity or mortality but also affects the socioeconomic and health care burden in China (Jia et al, 2018;Cui et al, 2020). Although tremendous efforts have been made to treat AD, no efficient disease-modifying therapeutics are available, partially because of the limited understanding of the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The annual total costs are predicted to reach United States $507.49 billion in 2030 and United States $1.89 trillion in 2050 (Jia et al, 2018). Taken together, the above statistics indicate that AD not only affects morbidity or mortality but also affects the socioeconomic and health care burden in China (Jia et al, 2018;Cui et al, 2020). Although tremendous efforts have been made to treat AD, no efficient disease-modifying therapeutics are available, partially because of the limited understanding of the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment of neurological and psychiatric diseases still focuses on symptomatic relief without targeting the underlying causal pathological molecular mechanisms. With an aging demography and rising incidences of AD [4] and PD [5], adequate and causal treatment with mild side-effects gains even more importance. Therefore, evaluating the role of different receptors and pathways in the homeostasis of oxidative stress in the central nervous system (CNS) might offer new opportunities in the therapy of neurological and psychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a complex and progressive neurodegenerative disorder that is considered the most common type of dementia [ 1 ]. In China, it was reported that 3.2% of people aged ≥ 60 years old were AD patients in 2018 [ 2 ]. With the rapid increase in the aging population, the yearly prevalence of AD has been predicted to increase to 5.35% in 2021 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, it was reported that 3.2% of people aged ≥ 60 years old were AD patients in 2018 [ 2 ]. With the rapid increase in the aging population, the yearly prevalence of AD has been predicted to increase to 5.35% in 2021 [ 2 ]. The etiology of AD has not been fully deciphered.…”
Section: Introductionmentioning
confidence: 99%